Job Security and Job Protection - Andrew E. Clark; Fabien Postel-Vinay (Institute for the Study of Labor (IZA), 2005)
We construct indicators of the perception of job security for various types of jobs in 12 European countries using individual data from the European Community Household Panel (ECHP). We then consider the relation between reported job security and OECD summary measures of Employment Protection Legislation (EPL) strictness on one hand, and Unemployment Insurance Benefit (UIB) generosity on the other. We find that, after controlling for selection into job types, workers feel most secure in permanent public sector jobs, least secure in temporary jobs, with permanent private sector jobs occupying an intermediate position. We also find that perceived job security in both permanent private and temporary jobs is positively correlated with UIB generosity, while the relationship with EPL strictness is negative: workers feel less secure in countries where jobs are more protected. These correlations are absent for permanent public jobs, suggesting that such jobs are perceived to be by and large insulated from labor market fluctuations.
Keywords: J65; J28; I31; 330; perceived job security; Employment Protection Legislation; Unemployment Insurance Benefits; Arbeitsplatzsicherung; Arbeitnehmerschutz; Kündigungsschutz; Arbeitslosenversicherung; Meinungsforschung; EU-Staaten